Analysis Of The Role Of Information Technology In Strengthening Islamic Religious Education In Pesantren: A Study Of Digital Transformation - Saputro, Muhamad Rikza; Arif, Mahmud (The Islamic Education and Multiculturalism Foundation, 2025)
Digital transformation has brought significant changes in various aspects of life, including in Islamic religious education in pesantren. As an educational institution that plays an important role in shaping the religious and cultural identity of Indonesian society, pesantren face challenges in adjusting to the development of information technology. This study aims to analyze the role of information technology in Islamic religious education in pesantren, including the challenges faced, strategies to overcome obstacles, and the impact on the learning process and pesantren culture. This research uses a qualitative method with a phenomenological approach. The research objects were Askhabul Kahfi and Roudlotul Muttaqin Islamic Boarding Schools in Semarang City. Data were collected through observations, interviews, and document studies, and analyzed using inductive and deductive approaches to find emerging patterns and meanings. Data validity was guaranteed through the triangulation method. The results show that pesantren have adopted information technology through the use of online platforms, learning applications, and digital resources to improve teaching effectiveness. However, the implementation of digital transformation is faced with infrastructure limitations, shifts in traditional pesantren culture, and curriculum adjustments. To overcome these challenges, it is necessary to increase the accessibility of technology, training for teachers and students, and the integration of Islamic values in the digital context. The impact can be seen in the changing roles of teachers and students as well as the shifting pesantren culture in religious learning. In conclusion, digital transformation makes a positive contribution to Islamic religious education in pesantren, although adaptation efforts are needed to remain in line with the traditional values upheld.